Do improved biomass cookstove interventions improve indoor air quality and blood pressure? A systematic review and meta-analysis. (1st December 2021) - Kumar, Nitya; Phillip, Eunice; Cooper, Helen; Davis, Megan; Langevin, Jessica; Clifford, Mike; Stanistreet, Debbi
Abstract: Objectives: This systematic review and meta-analysis evaluates the most recent evidence to examine whether use of improved biomass cookstoves in households in low-middle income countries results in reduction in mean concentrations of carbon monoxide (CO) and particulate matter of size 2.5 μm (PM2.5 ) in the cooking area, as well as reduction in mean systolic (SBP) and diastolic blood pressure (DBP) of adults using the cookstoves when compared to adults who use traditional three stone fire or traditional biomass cookstoves. Methods: We searched databases of scientific and grey literature. We included studies if published between January 2012 and June 2021, reported impact of ICS interventions in non-pregnant adults in low/middle-income countries, and reported post-intervention results along with baseline of traditional cookstoves. Outcomes included 24- or 48-h averages of kitchen area PM2.5, CO, mean SBP and DBP. Meta-analyses estimated weighted mean differences between baseline and post-intervention values for all outcome measures. Results: Eleven studies were included; ten contributed estimates for HAP and four for BP. Interventions lead to significant reductions in PM2.5 (−0.73 mg/m 3, 95% CI: −1.33, −0.13), CO (−8.37 ppm, 95%CI: −13.20, −3.54) and SBP (−2.82 mmHg, 95% CI: −5.53, −0.11); and a non-significant reduction in DBP (−0.80 mmHg, 95%CI: −2.33, 0.73), when compared to baseline of traditional cookstoves. Except for DBP, greatest reductions in all outcomes came from standard combustion ICS with a chimney, compared to ICS without a chimney and advanced combustion ICS. Conclusion: Among the reviewed biomass stove types, ICS with a chimney feature resulted in greatest reductions in HAP and BP. Graphical abstract: Image 1 Highlights: Among improved biomass cookstoves (ICS), the ones with chimneys result in most reductions in indoor air pollution. Chimney ICS associated with most reductions in systolic blood pressure in users. We recommend ICS with chimneys for communities without access to cleaner energy.